1989
DOI: 10.1104/pp.89.3.867
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Requirement of the Vanadate-Sensitive ATPase from Maize Roots Evaluated by Two Methods

Abstract: The activation of the vanadate-sensitive ATPase from maize (Zea mays L.) root microsomes by phospholipids was assessed by two different methods. First, the vanadate-sensitive ATPase was partially purified and substantially delipidated by treating microsomes with 0.6% deoxycholate (DOC) at a protein concentration of 1 milligram per milliliter. Vanadate-sensitive ATP hydrolysis by the DOC-extracted microsomes was stimulated up to 100% by the addition of asolectin. Of the individual phospholipids tested, phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…tergent [3][4][5][6][7][8][9][10][11][12][13][14] Detergent used for solubilization ATPane activity (.amol I"l!llS I,I". 'I'I'I'3,.N No+c~ld+cr 1~,~1 exceeded that obtained by soybean phospholipids (not shown), We have investigated the influence of lysoPC on some properties of H+-ATPase, The maximal stimulation by lysoPC occurred at pH 6,5, which ¢oin¢ided with the pH optimum of the enzyme, but the effect reversed to inhibitory at pH > 7,0 (Fig, 1), LysoPC also did not change tile sensitivity of tile enzyme to its specific inhibitor vanadate, We also found that lysoPC had no effect on the acid phosphatase activity of plasma membrane (Table III).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…tergent [3][4][5][6][7][8][9][10][11][12][13][14] Detergent used for solubilization ATPane activity (.amol I"l!llS I,I". 'I'I'I'3,.N No+c~ld+cr 1~,~1 exceeded that obtained by soybean phospholipids (not shown), We have investigated the influence of lysoPC on some properties of H+-ATPase, The maximal stimulation by lysoPC occurred at pH 6,5, which ¢oin¢ided with the pH optimum of the enzyme, but the effect reversed to inhibitory at pH > 7,0 (Fig, 1), LysoPC also did not change tile sensitivity of tile enzyme to its specific inhibitor vanadate, We also found that lysoPC had no effect on the acid phosphatase activity of plasma membrane (Table III).…”
Section: Resultsmentioning
confidence: 99%
“…When considering different ways of regulation, the effects of lipids on this integral enzyme are of special interest. The lipid dependence of the plasma membrane H +-ATPase activity has been previously demonstrated, both on partially delipidated [3] and solubilized preparations [4,5]. The enzyme reactivation by the different phospholipids revealed that the lysoPC was the most powerful activator in plasma membrane preparations of plants and yeast [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…30-35%) in the plasma membrane (10,14) and activated ATPase activity (Table I) (10). Although previous studies have examined the requirement of phospholipids to induce the ATPase activity using delipidated membrane vesicles (2), in this study we have completely solubilized the ATPase with a two-step procedure using deoxycholate and zwittergent prior to lipid additions. Serrano et al (18) performed a less extensive examination of the lipid requirements of a cholate-extracted preparation of the plant plasma membrane H+-ATPase and the protein content of this preparation was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for regulation of the ATPase by auxin is unknown (17). In our previous paper (10) and other reports (2,3,18), plasma membrane H+-ATPase was shown to require phospholipids for its activation, indicating that its activity may be regulated by interactions between this protein and the phospholipid environment in the plasma membrane. However, the effects…”
Section: Introductionmentioning
confidence: 99%
“…No effect Arabidopsis thaliana Gomès et al (1996) Spinacia olerancea Johansson et al (1994) Glycerolipids Asolectin Stimulation Oryza sativa Kasamo (1990) Spinacia olerancea Johansson et al (1994) Vigna radiata Kasamo and Nouchi (1987), Kasamo and Yamanishi (1991) Zea mays Brauer and Tu (1989) Phosphatidylcholine (PC) Stimulation Avena sativa Serrano et al (1988) Oryza sativa Kasamo (1990) Vigna radiata Kasamo and Nouchi (1987), Kasamo and Yamanishi (1991) Phosphatidylglycerol (PG) Stimulation Avena sativa Serrano et al (1988) Oryza sativa Kasamo (1990) Raphanus sativus Coccuci and Marré (1984) Vigna radiata Kasamo and Nouchi (1987), Kasamo and Yamanishi (1991) Zea mays Brauer and Tu (1989) Phosphatidylserine (PS) Stimulation Avena sativa Serrano et al (1988) Oryza sativa Kasamo (1990) Raphanus sativus Coccuci and Marré (1984) Vigna radiata Kasamo and Nouchi (1987), Kasamo and Yamanishi (1991) Zea mays Brauer and Tu (1989) Phosphatidic acid (PA) Stimulation Avena sativa Serrano et al (1988) Zea mays Brauer and Tu (1989) Inhibition Oryza sativa Kasamo (1990) Vigna radiata. Kasamo and Nouchi (1987), Kasamo and Yamanishi (1991) Plant Cell Rep…”
mentioning
confidence: 98%